1995
DOI: 10.1177/000456329503200404
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Time for Urine Collection for Detecting Early Kidney Abnormalities in Hypertensives

Abstract: SUMMARY.The aim of this study was to determine the most appropriate urine collection for detecting differences in the excretion rates of albumin, -y glutamyl trans peptidase (GGT) and N-acetyl-(j-D-glucosaminidase (NAGA) between normotensive subjects and hypertensive patients on treatment. Twenty treated hypertensive patients, mean (SEM, standard error of mean) age; 52·2 (6'2) years and 20 normotensive subjects, mean age 49· 2 (4'2) years, were studied in a consecutive sampling design. Urinary excretion rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Morning urine sample was suggested as the best sample for detecting early kidney abnormalities (Zuppi, et al, 1995). Spot morning urine sample was collected by each participant who was instructed to void the urine sample directly into 100 ml sterilized plastic container and centrifuged at 4500 rpm for 5 minutes, and then the clear supernatant was distributed in polyethylene vials (1.5 ml capacity).…”
Section: B) Biological Sampling and Methodsmentioning
confidence: 99%
“…Morning urine sample was suggested as the best sample for detecting early kidney abnormalities (Zuppi, et al, 1995). Spot morning urine sample was collected by each participant who was instructed to void the urine sample directly into 100 ml sterilized plastic container and centrifuged at 4500 rpm for 5 minutes, and then the clear supernatant was distributed in polyethylene vials (1.5 ml capacity).…”
Section: B) Biological Sampling and Methodsmentioning
confidence: 99%
“…Morning urine was suggested as the best sample for detecting early kidney abnormalities (Zuppi et al, 1995). Spot morning urine sample was collected by each participant who was instructed to void the urine sample directly into 100 mL metal-free polyethylene bottle.…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Many additional studies have also found that γ-GT [16,17], albumin [16][17][18][19][20], and NAG [18,21,22] excretion rates are significantly higher during the day than overnight. Some studies cite urinary flow rate as a possible cause for this finding [20,21,23].…”
Section: Introductionmentioning
confidence: 97%